Предмет: Математика, автор: zagrebelnaya1988

Обчислити вираз 2 3/5+1 3/5
7-3 2/7
2 5/9-1 7/9
(3 2/4+1 2/4)-(3 2/7-1 5/7)

Ответы

Автор ответа: dashulka22222
0

Пошаговое объяснение:

2 \frac{3}{5}  + 1 \frac{3}{5}  = (2 + 1) + ( \frac{3}{5}  +  \frac{3}{5} ) = 3 +  \frac{6}{5}  = 3 + 1 +  \frac{1}{5}  = 4 \frac{1}{5}

7 - 3 \frac{2}{7}  = 6 + 1 - 3 -  \frac{2}{7}  = (6 - 3) + ( \frac{7}{7}  -  \frac{2}{7} ) = 3 +  \frac{5}{7}  = 3 \frac{5}{7}

2 \frac{5}{9}  - 1 \frac{7}{9}  = (2 - 1) +  (\frac{5}{9}  -  \frac{7}{9} ) =  \frac{9}{9}  +  \frac{5}{9}  -  \frac{7}{9}  =  \frac{7}{9}

(3 \frac{2}{4}  + 1 \frac{2}{4} ) - (3 \frac{2}{7}  - 1 \frac{5}{7} ) = 4 \frac{4}{4}  - (2 +  \frac{9}{7}  - 1 -  \frac{5}{7} ) = 5 - 1 -  \frac{4}{7}  = 4 -  \frac{4}{7}  = 3 +  \frac{7}{7}  -  \frac{4}{7}  = 3 \frac{3}{7}

Похожие вопросы
Предмет: Русский язык, автор: Аноним